Hight return-to-sport rate following traumatic spine injury in amateur athletes - Raisch, Philipp; Hirth, Tabea; Kreinest, Michael; Vetter, Sven Y.; Grützner, Paul Alfred; Jung, Matthias (BMC sports science, medicine & rehabilitation, 2024)
Data on the resumption of sporting activity (return-to-sport, RTS) after traumatic spine injuries are mainly available for elite athletes. This study aimed to determine the RTS rate in amateurs after spine injury and to identify factors possibly influencing RTS.